Productivity growth, firm turnover and new varieties - Thomas von Brasch; Diana-Cristina Iancu; Arvid Raknerud (Statistics Norway, Research Department, 2018)
We reconcile two different strands of the literature: the literature on how new goods impact prices and the literature on productivity growth and firm turnover. To our knowledge, this is the first paper to provide a fully consistent decomposition of aggregate productivity growth that identifies the contribution from new firms producing new varieties. We extend the estimator for the demand elasticity, proposed by Feenstra (1994) and supplemented by Soderbery (2015), in two dimensions: First, we create a two-stage estimation framework that exploits the boundary cases where simultaneity is not an issue, i.e. when supply is elastic or inelastic, to obtain a more efficient estimator. Second, we make it robust towards choice of reference unit. To illustrate the decomposition and estimator, we analyse the case of firm turnover in Norway, using panel data covering the period from 1995 to 2016 for manufacturing firms. Our results indicate that net creation of new varieties from firm turnover contributes by about one half percentage point to annual aggregate productivity growth.
Keywords: C43; E24; O47; 330; Aggregation; Productivity growth; Variety gains; Demand elasticity